2019
DOI: 10.14740/gr1179
|View full text |Cite
|
Sign up to set email alerts
|

Elevated International Normalized Ratio: A Risk Factor for Portal Vein Thrombosis in Cirrhotic Patients

Abstract: Background Portal vein thrombosis (PVT) is a complication that is commonly seen in patients with cirrhosis and an entity that leads to increased mortality in patients who undergo liver transplantation. This study aims to establish a link between an elevated international normalized ratio (INR) and the presence of PVT in a cohort of cirrhotic patients. Methods We retrospectively reviewed the electronic medical records of all patients diagnosed with cirrhosis in SBH Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…It is possible that the patient was already at an increased risk of PVT, as cirrhosis is a well-known risk factor. [21][22][23][24] Overall, comparable safety and no excessive platelet increase were observed with lusutrombopag treatment for 7 days regardless of the timing of the discontinuation criteria application. These findings suggest that the role of platelet monitoring in lusutrombopag discontinuation might be limited to helping to ensure treatment safety, such as avoiding thrombosis due to excessive increase of platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the patient was already at an increased risk of PVT, as cirrhosis is a well-known risk factor. [21][22][23][24] Overall, comparable safety and no excessive platelet increase were observed with lusutrombopag treatment for 7 days regardless of the timing of the discontinuation criteria application. These findings suggest that the role of platelet monitoring in lusutrombopag discontinuation might be limited to helping to ensure treatment safety, such as avoiding thrombosis due to excessive increase of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the case of PVT in A/B‐2 was the only severe and serious TEAE considered potentially related to the study drug. It is possible that the patient was already at an increased risk of PVT, as cirrhosis is a well‐known risk factor 21–24 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we considered the possibility of a correlation between blood platelet count and PVT volume. Some reports indicated that the increased risk of PVT in cirrhosis is associated with decreased liver function (Child–Pugh score B/C) [ 7 ], low serum albumin [ 24 ], and increased prothrombin time [ 25 ]. However, these factors had no significant impact on the PVT volume in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, for cirrhosis patients who had undergone splenectomy, the incidence of PVT after surgery was 37.7% (49/130), and an increased platelet count has been described as a risk factor [ 25 ]. Another report also revealed that the platelet count was significantly higher in the PVT group (mean platelet count, 399.3 × 10 9 /L) than in the non-PVT group (mean platelet count, 296.9 × 10 9 /L) after laparoscopic splenectomy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, hepatoduodenal ligament massage prevented a reduction in portal vein flow, decreasing the risk of portal vein thrombosis after hepatectomy. Portal vein thrombosis affects the coagulation system, especially PT % [21]. In the massage group, the PT % was higher than that in the nonmassage group after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%